PENGGUNAAN PERMAINAN TRADISIONAL EGRANG BATOK KELAPA DALAM MENINGKATKAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI PAUD AYUNI TEMBUNG - Pamela, Rika Sri; Daulay, Nurussakinah; Pulungan, Enny Nazrah (Raudhah - Proud To Be Professional, 2024)
This research was carried out at PAUD Ayuni Tembung. Another problem in this research is what obstacles children face when playing the traditional game of coconut shell stilts in the gross motor development of children aged 5-6 years at PAUD Ayuni Tembung. The aim of this research is to determine the obstacles faced by children when playing the traditional game of coconut shell stilts in the gross motor development of children aged 5-6 years at PAUD Ayuni Tembung. The research method used is "Classroom Action Research" (PTK). Based on the results of research that has been conducted, playing on coconut shell stilts can improve the gross motor skills of group B children at PAUD Ayuni Tembung. The child's balance in the initial condition was 21.43%, in the first cycle it increased, the child's balance became 67.86%. The child's strength in the initial condition was 17.86%, in cycle I it increased, the child's strength became 64.29%, in cycle II it increased, the child's strength became 96.43%. The child's agility in the initial condition was 14.29%, in the first cycle it increased, the child's agility became 57.14%, in the second cycle it increased, the child's agility became 96.43%. Keywords: traditional coconut shell stilt game, rough motorbike This research was carried out at PAUD Ayuni Tembung. Another problem in this research is what obstacles children face when playing the traditional game of coconut shell stilts in the gross motor development of children aged 5-6 years at PAUD Ayuni Tembung. The aim of this research is to determine the obstacles faced by children when playing the traditional game of coconut shell stilts in the gross motor development of children aged 5-6 years at PAUD Ayuni Tembung. The research method used is "Classroom Action Research" (PTK). Based on the results of research that has been conducted, playing on coconut shell stilts can improve the gross motor skills of group B children at PAUD Ayuni Tembung. The child's balance in the initial condition was 21.43%, in the first cycle it increased, the child's balance became 67.86%. The child's strength in the initial condition was 17.86%, in cycle I it increased, the child's strength became 64.29%, in cycle II it increased, the child's strength became 96.43%. The child's agility in the initial condition was 14.29%, in the first cycle it increased, the child's agility became 57.14%, in the second cycle it increased, the child's agility became 96.43%. Keywords: traditional coconut shell stilt game, rough motorbike